(untitled) (Лучшие интеллектуальные исследования, 2024)
Abstract: This article is devoted to the study of strategies for the development of tailoring in vocational education. The article highlights the importance of training qualified personnel in the field of tailoring, the combination of practical and theoretical knowledge, and the need to modernize the educational process. Also, key strategies such as introduction of modern technologies, adaptation of educational programs to the needs of production, use of international experiences and strengthening of cooperation with sewing enterprises will be discussed. These strategies are important in improving the quality of vocational education and preparing competitive professionals for the garment industry.